Drone Injuries and Safety Recommendations - Serap Gorucu; Yiannis Ampatzidis (EDIS)
This publication presents drone-related injury statistics and safety recommendations to prevent drone-related injuries. Written by Serap Gorucu and Yiannis Ampatzidis, and published by the UF/IFAS Department of Agricultural and Biological Engineering, June 2021.